Green Synthesis Gold Nanoparticles using Bioreductor of Butterfly Pea (Clitoria ternatea L.) Leaf Extract as an Antioxidant - Fernanda, Cintya Dita; Taufikurohmah, Titik (Jurnal Pijar Mipa, 2024)
Gold nanoparticles are inorganic metal materials in suspended solutions with a particle size reduction process to the 5-400 nm nanoscale range. Gold nanoparticles can be synthesized using the green synthesis method using a bioreductor of butterfly pea leaf infusion extract, which can be used as an antioxidant. This study aimed to determine the characteristics of gold nanoparticles using a UV-Vis spectrophotometer and TEM and to determine the antioxidant strength of gold nanoparticles through the IC50 value. This study used 20, 10, 5, and 2.5 ppm concentration variations. The results of the characterization of gold nanoparticles using a UV-Vis spectrophotometer showed a maximum wavelength of 550 nm, and the results of the TEM test showed a particle diameter of 6.58 nm. The antioxidant activity test was carried out using the 1,1-diphenyl-2-picryhydrazyl (DPPH) quenching method, resulting in % quenching at a concentration of 20, 10, 5 and 2.5 ppm of 76.3; 70.6; 85.5; and 92.9% and an IC50 value of 0.25 ppm which is included in strong antioxidants. It can be concluded that gold nanoparticles synthesized using butterfly pea leaf extract have the potential to be an effective antioxidant agent.